If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 4 + p Solving 1 = 4 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 1 + -1p = 4 + p + -1p Combine like terms: p + -1p = 0 1 + -1p = 4 + 0 1 + -1p = 4 Add '-1' to each side of the equation. 1 + -1 + -1p = 4 + -1 Combine like terms: 1 + -1 = 0 0 + -1p = 4 + -1 -1p = 4 + -1 Combine like terms: 4 + -1 = 3 -1p = 3 Divide each side by '-1'. p = -3 Simplifying p = -3
| 8x^2-12y+4=y+10 | | cos(3o+20)=0.2 | | 4+3x+6=4x-5 | | x+(-10)=-22 | | 27-7r=-(1+3r) | | 20+2p=8+6(-8+2p) | | -5(a+6)=-14-7a | | 2y^2+14=104 | | x(5)=-5-1 | | 2(x+6)=3(x+4)+5 | | 180(n-1)=900 | | -84=7(p-4) | | -105=-7(1-2r) | | -75-18v=-70 | | =9p^5q+6p^4-15p^2q^4 | | -84=6(n-7) | | 2sinxta*n*x-3=0 | | ln(1-x)=2 | | 8m-21=51 | | 8x+8=4-x | | -3n+2=20 | | 2z+5=5z-4z | | -24=3m | | 3.4x+7=10 | | -17+v=-19 | | 19=n+8 | | 13.2-4.7x=-8.3-2.2x | | 2.8(x+4.9)=18.2 | | 12x^2=-27x | | -3v^2+7v-5=v^2+6v+2 | | 24x^2=36x | | 12(-1)-4y=-24 |